High-risk HPV prevalence among women undergoing cervical cancer screening: Findings a decade after HPV vaccine implementation in British Columbia, Canada. Issue 36 (23rd August 2021) - Litwin, Charles; Smith, Laurie; Donken, Robine; Krajden, Mel; van Niekerk, Dirk; Naus, Monika; Cook, Darrel; Albert, Arianne; Ogilvie, Gina
Highlights: First estimates of HPV prevalence 10 years post school-based vaccination in BC. Non-statistically significant decline in prevalence of HPV16/18 post-vaccination. Changes in screening guidelines may underestimate the vaccination program impact. Abstract: Background: British Columbia (BC) introduced a publicly funded, school-based human papillomavirus (HPV) immunization program in 2008 with the quadrivalent vaccine. In 2010/2011, a baseline evaluation of HPV prevalence was conducted among women undergoing cervical cancer screening. After 10 years of publicly funded HPV vaccination, HPV-type prevalence was re-evaluated. Methods: From August 2017 to March 2018, 1107 physicians were invited to return cytobrushes used during routine Pap screening to the Cervical Cancer Screening Laboratory for HPV testing. Only age or year of birth was collected. Specimens were screened for high-risk HPV (hrHPV) and positive samples were genotyped. HPV type prevalence was compared for females 15–22 yrs (those eligible for the school-based vaccination) and 23+ yrs (ineligible for school-based vaccination) for the 2010/2011 and the 2017/2018 data. Results: There were 3309 valid samples received for testing; of these, 3107 were included in the analysis. The overall hrHPV prevalence was 12.2% (95% CI 11.3–13.3) in 2010/11, and 12.0% (95% CI 10.9–13.2) in 2017/18. For the 15–22 age group, the prevalence for any hrHPV was 26.8% (95% CI 23.1–30.8) in 2010/11 and 25.4% (95% CI 15.3–37.9) in 2017/18. For those aged 15–22, HPV16 prevalence in 2010/11 was 8.8% (95% CI 6.5–11.5) and in 2017/18 was 6.3% (95% CI 1.8–15.5), with corresponding figures for HPV18 3.7% (95% CI 2.3–5.7) and 0% (95% CI 0.0–5.7), respectively. For all hrHPV types, there were no statistically significant differences between the 2010/11 and 2017/18 periods. Conclusions: This study illustrates the prevalence of hrHPV in BC over time in women undergoing cervical cancer screening, where an indication of a decline in HPV16/18 is seen in vaccine eligible women.